Exploring Digital Platforms for Cognitive Behavioral Therapy: A Bibliometric Review - Loso Judijanto; Yossy Dwi Erliana; Lukmanul Hakim; Ayuning Atmasari; Aisyah Putri Rawe Mahardika (Westscience Press, 2025)
This bibliometric study explores the extensive body of literature on digital platforms for Cognitive Behavioral Therapy (CBT), examining scholarly patterns, themes, and global contributions to the field. Utilizing Scopus data analyzed through VOSviewer, the study maps out keyword frequency, co-occurrence, author collaborations, and country contributions, revealing key insights into the evolution of digital CBT. The findings underscore a significant shift towards the use of mobile health applications and web-based interventions, highlighting the role of advanced technologies like machine learning and big data in personalizing and enhancing mental health treatments. The study also illustrates robust international collaborations, particularly among leading researchers from the United States, China, and India, who are pivotal in advancing the digital mental health agenda. Despite promising advancements, challenges such as data privacy, the digital divide, and integration into clinical practice persist. The study concludes that digital CBT holds substantial promise for revolutionizing mental health care by improving accessibility and personalization but requires ongoing research and innovation to overcome existing barriers and fully integrate into mainstream health services.